The Effect of Business Location and Product Diversity on Consumer Intention to Purchase - Paimin, Iwan; Musprihadi, Ribut (Faculty of Economics and Business UNTAG Semarang, 2024)
This study aimed to determine the effect of location of business and product diversity on purchasing intention. The population was all customers of the Lokapita Semarang Knitting Business Group. The research sample was set at 100 people. The determination of sample members used the Purposive Sampling technique, while the data collection technique used a questionnaire. Furthermore, data analysis was carried out using multiple linear regressions. The results showed that location and product diversity can explain consumer purchasing interest. The further finding showed that location and product diversity had a positive effect on purchasing intention statistically acceptable. The managerial implication of the study is a better product and business location should be developed so that consumers will view buying products at the corporate.